Learning Classroom Environment and Mufrodat Memory Ability of Madrasah Students in Palembang - Jumhur, Jumhur (An-nida: Jurnal Pendidikan Islam, 2022)
The physical environment of the class and motivation is one of the factors that can affect students' mastery of memory and in class there are many pictures that support learning and the teacher gives motivation to students. This study aims to determine whether or not there is influence of the physical environment of the class and learning motivation on the ability of mufrodat's memory. This research is a quantitative research. The method used is a survey research method. This research was conducted at MI Daarul Aitam Palembang. The sample used was students in grades 4 and 5, totaling 58. Data collection techniques used questionnaires and tests. The data analysis technique used in this study is multiple regression with product moment correlation. The results of the study show that the elements in the physical environment, namely pictures, writing and illustrations in the classroom affect students' ability to memorize mufrodat. In addition, it was also produced that the ability of students' memory of mufrodat was also influenced by the elements in students' learning motivation.